Prognostic profile of systemic sclerosis: analysis of the clinical EUSTAR cohort in China - Hu, Shasha; Hou, Yong; Wang, Qian; Li, Mengtao; Xu, Dong; Zeng, Xiaofeng (Arthritis research & therapy, 2018)
Systemic sclerosis is a disease that has significant clinical heterogeneity. This study aims to determine the causes and risk factors of death in a single center European League Against Rheumatism Scleroderma Trials and Research Group (EUSTAR) cohort at the Peking Union Medical College Hospital (PUMCH) in China. Patients clinically diagnosed with systemic sclerosis (SSc) between Feb 2009 and Dec 2015 were prospectively recruited from the EUSTAR database and Chinese Rheumatism Data Center (CRDC) of the PUMCH. Baseline and follow-up data were collected. Kaplan-Meier analysis was used to estimate survival, and Cox proportional hazards regression analysis was used to identify factors associated with mortality. A total of 448 patients were included in the cohort, of whom 56.7% had limited cutaneous systemic sclerosis (lcSSc). The average age at diagnosis was 42.8 ± 12.1 years. The prevalence of interstitial lung disease (ILD) was 382/447 (85.5%). Among 402 patients, 348 of them took glucocorticoid during the disease course; 374 patients received immunosuppressors. Across 2167 patient-years, 40 patients died. Of these, 27 deaths were attributable to SSc, with pulmonary arterial hypertension (PAH) being the leading cause of death. The median survival time was 53 months. Survival rates from disease diagnosis were 97.0%, 94.6%, 91.1% and 87.8% at 1, 3, 5 and 10 years, respectively. Independent prognostic factors for mortality were PAH (HR 6.248, 95% CI 2.855, 13.674) and arrhythmia (HR 4.729, 95% CI 1.588, 14.082). Tripterygium wilfordii Hook F (TwHF) (log-rank test 7.851, p 0.005) and methotrexate (MTX) (log-rank test 7.925, p = 0.005) were found in survival analysis to be protective treatments against mortality. Patients who used cyclophosphamide (CTX) during the disease course had poorer prognosis (log-rank test 5.177, p = 0.023). In china, although there is a high prevalence of ILD in patients with SSc (85.5%), most of them have reserved pulmonary function, which means that interstitial lung disease (ILD) is not the most important factor in the death of patients with SSc and also is not a risk factor for poor prognosis. Only ILD with pulmonary dysfunction is associated with poor outcome. The 10-year cumulative rate (87.8%) in patients with SSc in China is slightly lower than the Europe, and pulmonary arterial hypertension (PAH) and arrhythmia at baseline are independent prognostic factors, whereas PAH instead of ILD is the leading cause of death in patients with SSc. Interestingly, the Chinese traditional medicine TwHF, as a protective factor for survival deserves further study.